2022
DOI: 10.1002/ase.2221
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and clinical anatomical education: Promises and perils

Abstract: Anatomy educators are often at the forefront of adopting innovative and advanced technologies for teaching, such as artificial intelligence (AI). While AI offers potential new opportunities for anatomical education, hard lessons learned from the deployment of AI tools in other domains (e.g., criminal justice, healthcare, and finance) suggest that these opportunities are likely to be tempered by disadvantages for at least some learners and within certain educational contexts. From the perspectives of an anatomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 110 publications
0
36
0
Order By: Relevance
“…According to the latest research reports, there are a few areas in Anatomy where one can find the novelty of AI and these include (1) studying human variations, (2) in healthcare practice, (3) diversity and social justice, (4) student support and (5) student learning [ 77 ]. It has also been suggested that there should be proper training and support for Anatomy educators regarding how to interpret AI student monitoring and when to depend “on the humanness of education over the data-driven recommendations” [ 77 ].…”
Section: Future Novel Scope Of Artificial Intelligence In Anatomy Edu...mentioning
confidence: 99%
See 3 more Smart Citations
“…According to the latest research reports, there are a few areas in Anatomy where one can find the novelty of AI and these include (1) studying human variations, (2) in healthcare practice, (3) diversity and social justice, (4) student support and (5) student learning [ 77 ]. It has also been suggested that there should be proper training and support for Anatomy educators regarding how to interpret AI student monitoring and when to depend “on the humanness of education over the data-driven recommendations” [ 77 ].…”
Section: Future Novel Scope Of Artificial Intelligence In Anatomy Edu...mentioning
confidence: 99%
“…According to the latest research reports, there are a few areas in Anatomy where one can find the novelty of AI and these include (1) studying human variations, (2) in healthcare practice, (3) diversity and social justice, (4) student support and (5) student learning [ 77 ]. It has also been suggested that there should be proper training and support for Anatomy educators regarding how to interpret AI student monitoring and when to depend “on the humanness of education over the data-driven recommendations” [ 77 ]. It has been suggested that focusing artificial intelligence-infused Anatomy education (AIEd) development on challenging complicated anatomical areas such as the middle ear or the pterygopalatine fossa, areas where human instructors often struggle, could be beneficial [ 77 ].…”
Section: Future Novel Scope Of Artificial Intelligence In Anatomy Edu...mentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the intricate concepts and situations presented in medical education necessitates expertise in a variety of disciplines. Complicated medical situations and ethical or professional dilemmas may be difficult for AI to address effectively 10.…”
mentioning
confidence: 99%